PERANCANGAN BUSANA READY TO WEAR DELUXE DENGAN INSPIRASI THE CULTURE OF ANIMAL SPIRIT DARI SUKU INDIAN - Yovita Sabatini Daeli; Dewi Isma Aryani; Indra Janty (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2019)
Indian tribes are native of North America who are famous for tradition, lifestyle, art form, and belief as a cultural tradition. One of the traditions of Indian tribes' beliefs against spirit of animal related to the Indian tribes' religion is animism. In the belief of the spirit of animals there are several animals that are considered important as an aspect of Indian life, namely: eagle, wolves, bears, and bison are symbolized as the basis of the structure life for Indians. Merging the symbol of trust based on the direction of the wind, season, elements, and the color of each symbol from animal spirits which became the inspiration for designing fashion collections ready-to-wear deluxe titled OTODEM. Through the OTODEM collection displayed ethnic nuances but still modern in terms of form or fashion pieces. The concept applied to adaptive design forms from animal spirits, namely: eagle, wolf, bear, and bison in every outfit and from the symbol of the direction of the wind, seasons, elements, and color. Symbols or symbols are applied to clothing through technique polyflex screen printing and flocking on parts of symbols or symbols, Macrame and stitching techniques are used to show characteristics from Indian clothing. The aim is to strengthen the appearance and memorable similar to the symbol or symbol of the Indian Tribe. The ready-to-wear collection deluxe is shown for men and women with aged 25-35 years, have a profession as an entertainer like musicians, artists, designers and public figures with characters brave, likes challenges and likes to try new things, likes things related to culture / ethnicity, and domiciled in major cities of Indonesia. Keywords: animal, belief, ethnic, India Tribes, symbol .